7 Tesla MRI of Balo's concentric sclerosis versus multiple sclerosis lesions - Behrens, Janina R.; Jarius, Sven; Wildemann, Brigitte (Annals of Clinical and Translational Neurology, 2018)
Background: Baló's concentric sclerosis (BCS) is a rare condition characterized by concentrically layered white matter lesions. While its pathogenesis is unknown, hypoxia-induced tissue injury and chemotactic stimuli have been proposed as potential causes of BCS lesion formation. BCS has been suggested to be a variant of multiple sclerosis (MS). Here, we aimed to elucidate similarities and differences between BCS and MS by describing lesion morphology and localization in high-resolution 7 Tesla (7 T) magnetic resonance imaging (MRI) scans. Methods: Ten patients with Baló-type lesions underwent 7 T MRI, and 10 relapsing remitting MS patients served as controls. The 7 T MR imaging protocol included 3D T1-weighted (T1w) magnetization-prepared rapid gradient echo, 2D high spatial resolution T2*-weighted (T2*w) fast low-angle shot and susceptibility-weighted imaging. Results: Intralesional veins were visible in the center of all but one Baló-type lesion. Four Baló-type lesions displayed inhomogeneous intralesional T2*w signal intensities, which are suggestive of microhemorrhages or small ectatic venules. Eight of 10 BCS patients presented with 97 additional lesions, 36 of which (37%) had a central vein. Lesions involving the cortical gray matter and the U-fibers were not detected in BCS patients. Conclusion: Our findings support the hypothesis that BCS and MS share common pathogenetic mechanisms but patients present with different lesion phenotypes.